A NEW SPECIES OF ACAMPTOPOEUM FROM COLOMBIA (HYMENOPTERA: ANDRENIDAE: PANURGINAE) - GONZÁLEZ VÍCTOR H. (Caldasia)
A new species of the panurginae bee genus Acamptopoeum (Andrenidae: Calliopsini), from a xeric highland area in the Eastern Andes of Colombia is described and illustrated. Acamptopoeum fernandezi sp. nov., can be recognized by the black integument without blue or green reflections and the short, sparse white pubescence on the body, not forming apical bands of setae on metasoma. A. prinii is also reported for the first time for Colombia.